Numerical investigation of nanoscale electromechanical response in a ferroelectric perovskite through an atomistic field theory. (17th February 2019) - Li, Meng; Lin, Liqiang; Guo, Ruyan; Bhalla, Amar; Zeng, Xiaowei
Abstract: An atomistic field theory was introduced to study the electromechanical response in a ferroelectric perovskite at nanoscale. Based on a shell model potential, the polarization switching process of a ferroelectric perovskite PbTiO3 under electric field and mechanical loading was investigated. The simulation results showed that external electric field applied opposite to the initial polarization direction could result in 180° polarization switching in PbTiO3 nanostructures as the external electric field increased. On the other hand, mechanical loading applied parallel to initial polarization could cause 90° nanoscale polarization rotation in PbTiO3. Ultimately, the simulation results indicated that the coupled loads of electric field and mechanical loading would influence the polarization switching in PbTiO3 nanostructures.